Stirling-Engine in a Novel Alphagamma Configuration – a Key for Maintenance-free Operation - Frauscher Josef (EDP Sciences, 2021)
Since 2001, Frauscher Thermal Motors have been conducting research in the field of thermodynamic machines, in particular Stirling engines of various types. One important development step is the invention of a Stirling engine in an alphagamma® configuration. In this configuration, the expansion piston is designed as a differential piston with its ring surface connected to the cold volume. In this paper, the design advantages of the alphagamma® configuration in comparison with a traditional alpha configuration are shown analytically by using a polytropic model as a modification of the ideal adiabatic analysis. The findings were confirmed by also simulating the proposed alphagamma® configuration in a Sage model which was validated against experimental data with very good agreement. The results of both methods show that the counter-productive compression work can be reduced to almost zero – which makes the compression piston a displacer and explains the name alphagamma® – with the expansion work also reduced for the same net work output. As a consequence, the forces on the pistons, and thus, on the bearings can be significantly reduced, also leading to smaller piston side-loads, less friction and wear. The combination of all advantages allows the design of a mechanically sound and inexpensive machine.